Spatial distribution and associated factors of dropout from health facility delivery after antenatal booking in Ethiopia: a multi-level analysis - Melaku Yalew; Asiressie Molla; Getahun Gebre Bogale; Tesfaye Birhane; Mastewal Arefaynie; Yitayish Damtie; Bereket Kefale; Bezawit Adane (BMC, 2023)
Abstract Background Nowadays, retaining women in the continuum of care throughout the lifecycle: adolescence, pregnancy, childbirth, postpartum, and childhood in reproductive health is one of the recent global concerns. Most of the previous studies focused on individual-level factors and used classical logistic regression. Furthermore, it doesn't take into account its distribution. Therefore, this study aimed to assess spatial distribution, and associated factors of dropout from health facility delivery after antenatal booking among postpartum women in Ethiopia. Method Cross-sectional study by secondary analysis of the Ethiopian Mini Demographic and Health Survey (EMDHS) 2019 dataset was conducted among postpartum women. A total of 2882 women who gave birth 5 years prior to the survey were included. Sampling weight was applied and the analysis was done using STATA version 16. Aeronautical Reconnaissance Coverage Geographic Information System (ArcGIS) 10.8 software was used to map the cluster and attribute of dropout from health facility delivery and Global and local Moran's Index methods were used to assess the extent of clustering. Multi-level (two-level) logistic regression analysis was used and variables with a P value less than 0.5 were considered statistical significance. Adjusted odds ratio AOR) with a 95% confidence interval was used to show the strength and direction of the association respectively. Results Dropout from health facility delivery after ANC (Antenatal Care) booking in Ethiopia was 35.42%, 95% CI (33.70, 37.19), and it spatially clustered (Moran's index = 0.51, P value < 0.001). From individual-level variables: women who were primary educated [AOR = 0.70, 95% CI (0.49, 0.98)], secondary educated [AOR = 0.38, 95% CI (0.19, 0.73)], lived in the middle [AOR = 0.54, 95% CI (0.29, 0.98)], richer wealth [AOR = 0.37, 95% CI (0.18, 0.78)], richest wealth [AOR = 0.21, 95% CI (0.06, 0.74)], being counseled about pregnancy and childbirth complications [AOR = 0.52, 95% CI (0.34, 0.80)] and women who had four and above ANC visit [AOR = 0.52, 95% CI (0.38, 0.71)] were negatively associated with dropout. Whereas, second birth order [AOR = 2.62, 95% CI (1.40, 4.89)], 3-4th birth order [AOR = 4.92, 95% CI (2.82, 8.60)], above 4th birth order [AOR = 4.77, 95% CI (2.16, 10.53))] were positively associated with dropout. From community-level variables: mothers who lived in Afar [AOR = 2.61, 95% CI (1.08, 6.32)] and Oromia [AOR = 2.63, 95% CI (1.15, 6.02)] were positively associated with dropout from health facility delivery after ANC booking. Conclusions Dropout from health facility delivery after ANC booking was high as the government's effort and its spatial distribution in Ethiopia was clustered. Increased educational status of the mother, having four or more ANC visits, counseled about pregnancy and childbirth complications, and higher household wealth were negatively associated and higher birth order, and living in Oromia and Afar region were positively associated with dropout in Ethiopia. Strengthening women's education, encouraging women to complete ANC visits, being counseled them on pregnancy and childbirth complications, and improving family wealth status will be the recalled intervention areas of the government.